(untitled) (The Pakistan Development Review, 2017)
―When groups are adequately stated, everything is stated!‖1 Management of actions and interest groups has historically been sovereign‘s existentialist imperative. The paper revitalizes philosophical state autonomy debate and then narrows down its focus to capture extractive antics of as erratic a state as Pakistan. A typology of factions – captioned as Elites – operative in extractive realm of Pakistan is developed to round them in theory, identify their properties, and lay bare mechanics of intra-elite and elite-non-elite transactions. The paper seminally develops the rational actor dilemma confronting Pakistani elites and identifies the modes through which the dilemma plausibly resolves itself. The transactional engagement between Pakistan‘s internal and external rational actors is dissected to theorize that Pakistan essentially is an equilibrium consensus subsistence state thereby opening up vast vistas for future research. The paper concludes with the glum finding that Pakistan in its current essence and manifestation is fundamentally a captive state – beholden to elites of Pakistan. JEL Classification: H1 Keywords: State Autonomy; Elite Capture; Pakistan‘s Tax System; Pakistani Elites; Elites‘ Rational Actor Dilemma; Equilibrium Consensus Subsistence State; Captive State